Prior authorization by the Health Insurance Organizations in Iran - Mehrnaz Kheirandish; Zahra Gharibnaseri; Fatemeh Soleymani; Abbas Kebriaeezadeh (Tehran University of Medical Sciences, 2015)
Background: Health care improvement has had a critical role in increasing life expectancy throughout the world. The expenditures of research and development and also marketing for new pharmaceutical products are much higher than already existing medicines, resulting in higher prices for the former products. Therefore governments and health insurance organizations are interested in implementing policies that control drug prescription and utilization. One of these policies is Prior Authorization (PA). The main goal of PA is to reduce drug expenditures by substituting expensive medicines with less costly ones. PA policy has both scientific and economical aspects. The aim of this article is to assess the state of implementation of PA policy in Iran. There are several bodies to regulate medicines and their price in Iranian pharmaceutical market. There are two main insurance companies in Iran with similarities and differences in implementing this policy. Price ceiling and Reference Based Pricing are two main methods for implementing PA policy in Iran.